Ethics and its role in the development of business organization - BOUTOUBA, Mohamed; Hadj Amor, Fatima (Journal of Human Sciences, 2020)
If the idea of development did not imply on a moral dimension that ensure a good performance and effectiveness, there would not have been inherently a development problematic. However, with the variety of people's natures and the absence of the controller psychological feeling machine for the human being , it is not possible to know what is hiding within individuals from intentions and ideas. For this purpose, we find A. Sen., the economy Nobel Prize's laureate of 1998, who dealt with the ethical subject of economics, because this latter can be controlled only by a hidden psychological factor which is morality. It is obvious that the attention given to the problems of today’s' sustainable development and some tragic situations is not only due to purely economic considerations, but furthermore, we could notice, that there is a growing sense of moral responsibility towards ensuring sustainable development within the business organization. As probably, the fought experiences of Indonesia, Japan, Malaysia and China towards their interest in the moral component made it possible to achieve an efficient system of work that reached the development of all sectors.